Bonamia ostreae, parasite de l'huître plate, Ostrea edulis: sa position taxonomique parmi les parasites du groupe "microcell", analyses des interactions hôte/parasite chez plusieurs populations d'huîtres plates - Besnard-cochennec, Nathalie (Université de La Rochelle, 2001)
Bonamia ostreae is the causative agent of hemocyte disease. It has been detected first during mortalities occured in Franc in 1979. Bonamiosis spread rapidly among oysters farming in France and Europ. Another species, Bonamia sp. has been detected in New Zealand and Australia. These paasites were both included in the "microcell" group. This group contains 2 others parasites, Mikrocytos mackini affecting Crassostrea gigas in British Columbia (Canada) and M. roughleyi affecing Saccostrea glomerata in Australia. Structural and molecular caracterisation of all these parasites were realised. Results show tha B. ostreae, B. sp., B. exitiosus. Molecular tools are available for genus detection, Bonamia spp. and Mikrocytos and species identification (B. ostreae, B. exitiosus and M. roughleyi). Cell targets of Bonamia, the hemocytes were analysed by flow cytometer. Three hemocyte types were idenified using size and granularity parameters. Hemocyte distributions indicate that the agranular cells are majority. Four lectins allow to discriminate granular and agranular cells. Bonamia ostreae exhibit the same granulocyte sugar patterns on its cytoplasmic membrane suggesting that glycosylation are involved in adhesion mechanisms between hemocytes and B. ostrea and/or phagocytosis. Six intrahemocyte enzymatic activities and production of reactive oxygen were evaluated for each cell types. The different expressions are important in granulocytes. Large agranular and small hyalinocytes exhibit less activities. Different oyster populations were compared to identify cytologic parameters associated with resisnance status. Esterase and hydrogen peroxyde large agranular expressions are correlated with Bonamia restance. These parameters could be used as selective markers for Bonamia genetic selection programms. La Bonamiose, maladie due au protozaire Bonamia ostreae a été détectée en 1979 pour la première fois en Bretagne au cours d'épisodes de mortalité. Depuis, cette maladie s'est propagée à tous les centres ostréicoles français, ...